50th Anniversary Article: Multiaxial Fatigue Testing of Composites: From the Pioneers to Future Directions. (29th December 2014) - Quaresimin, M.
Abstract This paper presents an overview on the experimental investigation of the response of composite materials under multiaxial cyclic loading, starting from the pioneering works in the early 1970s to arrive to the research activities run in these days by the scientific community and concluding with the areas still open. The experimental techniques and sample geometries are compared, illustrating advantages and drawbacks of each solution, also with reference to the outcomes of the research. The influence of the main design parameters are illustrated, taking advantage of experimental results from the extensive investigation carried out in the last years at the University of Padova. Needs of future research are eventually addressed.